APLIKASI METODE GEOLISTRIK UNTUK MENGETAHUI SEBARAN BATUBARA DI KABUPATEN TULUNGAGUNG JAWA TIMUR - Rusli, Rusli; Azizah, Elvira; Basid, Abdul (Faculty of Science and Education, UIN Walisongo Semarang, 2020)
Research has been conducted aiming to determine the distribution of coal below the surface in Tulungagung Regency. The survey conducted in this study used a Wenner configuration resistivity geoelectric survey. Retrieval of geolithic resistivity data in the field of four trajectories. The results of data collection in the field oneach track are processed using 2D modeling in Res2dinv software. The results of the processing of the two-dimensional modeling are then interpreted. The structure of rock layers containing coal is shown by a yellow, red to dark purple scheme with a resistivity value of 75-350 ohm meters on the inside varying from 0 meters to 6.91 meters below the surface, spreading erratically and patching on each track.